Analisis Unsur Intrinsik dalam Cerpen “Angin dari Gunung” Karya A.A. Navis - Prasiska, Tiara Zalma; Abdurahman, Abdurahman (CV. ITTC INDONESIA, 2025)
This study aims to analyze the intrinsic elements of the short story “Angin dari Gunung” by A.A. Navis using a structural approach. The research employs a qualitative descriptive method through close reading, note-taking, and textual analysis. The findings reveal that the main theme of the story centers on the protagonist’s psychological struggle when dealing with social pressure and the desire for personal tranquility. The internal conflict experienced by the protagonist is reflected through inner monologues and narrative descriptions that contrast the serenity of the mountain with his emotional restlessness. The mountain setting functions symbolically as a space of quiet contemplation, yet it highlights the protagonist’s inability to escape his internal burdens. The progressive plot illustrates the character’s psychological development toward the realization that physical escape cannot resolve inner turmoil. This study concludes that the intrinsic elements—theme, characters, plot, setting, and conflict—work cohesively to construct the story’s overall meaning. Each element supports the narrative structure and reinforces the message regarding self-awareness, acceptance, and the complexity of human emotional experience.